Table Top Salt Triage In Improving Pre Hospital Triage Capacity And Disaster Victim Handling Preparedness - Christina Dewi Prasetyowati; Sri Wahyuni (Jurnal Smart Keperawatan, 2023)
Disasters have broad and complex impacts, both on humans and the surrounding environment. One of the challenges often faced in health management efforts in disaster areas is the lack of skills of nurses and other health workers in disaster victim preparedness and the ability to carry out pre hospital triage which will ultimately hamper health services. The knowledge and skills of nurses in handling disaster victims including conducting triage on victims are still in the sufficient category at 60%. In pre hospital situations, the correctness of officers in making triage decisions in handling victims has a very important role. The research objective was to determine the effect of the SALT triage table top in improving pre hospital triage capabilities and disaster victim handling preparedness. The research design used was a quasi experiment with a pre-post test with a control group. Sampling using purposive sampling technique. The number of respondents obtained was 78 people. The results of the Wilcoxon test showed a value of p = 0.000, which means that there is an influence of the SALT triage table top in increasing the ability of pre hospital triage and preparedness for handling disaster victims. Keywords: disaster; preparedness; pre hospital; table tops; triageTable Top Salt Triage Dalam Meningkatkan Kemampuan Triage Pre Hospital Dan Kesiapsiagaan Penanganan Korban BencanaABSTRAK Bencana memiliki dampak yang luas dan kompleks, baik terhadap manusia maupun lingkungan sekitarnya. Salah satu tantangan yang sering dihadapi dalam upaya penanggulangan kesehatan di daerah bencana adalah kekurangan ketrampilan perawat dan tenaga kesehatan lainnya dalam kesiapsiagaan penanganan korban bencana maupun kemampuan melakukan triage pre hospital yang akhirnya akan menghambat pelayanan kesehatan. Pengetahuan dan ketrampilan perawat dalam penanganan korban bencana termasuk melakukan triage terhadap korban masih berada pada kategori cukup sebesar 60%. Pada situasi pre hospital, kebenaran petugas dalam membuat keputusan triage dalam penanganan korban memiliki peran yang sangat penting. Tujuan penelitian untuk mengetahui pengaruh table top SALT triage dalam meningkatkan kemampuan triage pre hospital dan kesiapsiagaan penanganan korban bencana. Desain penelitian yang digunakan adalah quasi eksperiment dengan pre-post test with control group. Pengambilan sampel dengan menggunakan tehnik  purposive sampling. Responden yang didapatkan berjumlah 78 orang. Hasil uji Wilcoxon menunjukkan nilai p = 0,000 yang artinya ada pengaruh table top SALT triage dalam meningkatkan kemampuan triage pre hospital dan kesiapsiagaan penanganan korban bencana. Kata Kunci : bencana; kesiapsiagaan; pre hospital; table top; triage